On Some Hyperideals in Ordered Semihypergroups - Mohammad Yahya Abbasi; Bhavanari Satyanarayana; Poonam Kumar Sharma; Shahnawaz Ali; Abul Basar (Journal of New Theory, 2019)
In this paper, we study orderedhyperideals in ordered semihypergroups. Also, we study (m, n)-regular orderedsemihypergroups in terms of ordered (m, n)-hyperideals. Furthermore, we obtainsome ideal theoretic results in ordered semihypergroups.